Hubungan Minum Teh Terhadap Kejadian Anemia pada Ibu Hamil Trimester III di Puskesmas Ngaliyan Semarang - Noor Naini Choiriyah; Desi Soraya; Kristina Maharani (Calory Journal Medical Laboratory Journal, 2024)
Anaemia is a common issue during pregnancy, affecting not only pregnant women but also their foetuses and the birth process. Pregnant women are considered anaemic if their haemoglobin (Hb) levels fall below 11 g/dL, with a higher prevalence observed in the third trimester. One contributing factor to anaemia during pregnancy is tea consumption, as tea contains tannin compounds that can inhibit iron absorption. This study aims to investigate the correlation between tea consumption and the incidence of anaemia in pregnant women during the third trimester. An analytical observational research design with a cross-sectional approach was employed. The study was conducted among pregnant women in the third trimester at the Ngaliyan Health Centre from November to December 2023, with a total sample of 55 participants selected through purposive sampling. Data were analysed using both univariate and bivariate methods. The results revealed a significant relationship between tea consumption and the incidence of anaemia, with a p-value of 0.003 (p < 0.005). These findings suggest that tea consumption is associated with an increased risk of anaemia in pregnant women during the third trimester.